OR2H2 Activates CAMKKβ-AMPK-Autophagy Signaling Axis and Suppresses Senescence in VK2/E6E7 Cells - Ji Min Kim; Sina Dziobaka; Ye Eun Yoon; Ha Lim Lee; Ji Hyun Jeong; In-Ryeong Lee; Daniel Weidinger; Changwon Yang; Deokho Kim; Yalcin Gulperi; Cheol-Koo Lee; Jeongwon Sohn; et al. (MDPI AG, 2023)
Olfactory receptors are expressed in multiple extra-nasal tissues and these ectopic olfactory receptors mediate tissue-specific functions and regulate cellular physiology. Ectopic olfactory receptors may play key roles in tissues constantly exposed to odorants, thus the functionality of these receptors in genital tissues is of particular interest. The functionality of ectopic olfactory receptors expressed in VK2/E6E7 human vaginal epithelial cells was investigated. OR2H2 was the most highly expressed olfactory receptor expressed in VK2/E6E7 cells, and activation of OR2H2 by aldehyde 13-13, a ligand of OR2H2, increased the intracellular calcium and cAMP concentrations. Immunoblotting demonstrated that activation of OR2H2 by aldehyde 13-13 stimulated the CAMKKβ-AMPK-mTORC1-autophagy signaling axis, and that these effects were negated by OR2H2 knockdown. AMPK is known to regulate senescence; consequently, we investigated further the effect of aldehyde 13-13 on senescence. In H2O2-induced senescent cells, activation of OR2H2 by aldehyde 13-13 restored proliferation, and reduced the expression of senescence markers, P16 and P19. Additionally, aldehyde 13-13 induced apoptosis of H2O2-induced senescent cells, compared with non-senescent normal cells. In vivo, aldehyde 13-13 increased the lifespan of Caenorhabditis elegans and budding yeast. These findings demonstrate that OR2H2 is a functional receptor in VK2/E6E7 cells, and that activation of OR2H2 activates the AMPK-autophagy axis, and suppresses cellular aging and senescence, which may increase cellular health.